O lugar da comunicação escolar na implantação de um currículo bilíngue: um olhar dos educadores - Zen, Gracilene (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation investigates the perceptions of educators at Colégio Medianeira in Curitiba regarding the implementation of the bilingual education program introduced at the institution in 2019. The main objective was to gather and analyze the perceptions of the school community, particularly concerning communication about the program, aiming to increase engagement with the bilingual proposal. The study adopts a qualitative approach, employing a single case study, and is based on data collected through an online questionnaire and document analysis. The theoretical framework addresses concepts of bilingual education, with an emphasis on bilingual education within the Jesuit Education Network, school communication, and institutional engagement strategies. The research reveals that while educators acknowledge the importance of the bilingual program for the students' holistic development, challenges arise during implementation, such as: (i) lack of time for collaborative planning; (ii) the need for specific training in the additional language; and (iii) limitations in institutional communication. In response to these challenges, an intervention proposal was developed, focusing on a strategic internal communication plan aimed at improving information flow and strengthening educator engagement. The analysis highlights the significance of effective communication strategies, ongoing professional development, and integrated pedagogical planning for the successful consolidation of the bilingual program. The conclusions offer contributions toward strengthening educator engagement and ensuring successful program implementation, aligning it with the goals of holistic education and global citizenship.
Keywords: Educação bilíngue; Comunicação escolar; Gestão escolar; Língua adicional; Comunicação institucional; Bilingual education; School communication; School management; Additional language; Institutional communication; ACCNPQ::Ciências Humanas::Educação